Dynamics of auditory working memory - Kaiser, Jochen (Frontiers in Psychology, 2015)
Working memory denotes the ability to retain stimuli in mind that are no longer physically present and to perform mental operations on them. Electro- and magnetoencephalography allow investigating the short-term maintenance of acoustic stimuli at a high temporal resolution. Studies investigating working memory for non-spatial and spatial auditory information have suggested differential roles of regions along the putative auditory ventral and dorsal streams, respectively, in the processing of the different sound properties. Analyses of event-related potentials have shown sustained, memory load-dependent deflections over the retention periods. The topography of these waves suggested an involvement of modality-specific sensory storage regions. Spectral analysis has yielded information about the temporal dynamics of auditory working memory processing of individual stimuli, showing activation peaks during the delay phase whose timing was related to task performance. Coherence at different frequencies was enhanced between frontal and sensory cortex. In summary, auditory working memory seems to rely on the dynamic interplay between frontal executive systems and sensory representation regions.